Hidden Holocaust – Documents, Interpretations and Testimonies - Bajić, Predrag Đ. (Napredak, 2022)
The study Jasenovac – Auschwitz of the Balkans gathers in one place numerous documents, interpretations and testimonies about the notorious camp system in the territory of the former Independent State of Croatia. Behind this book, at the same time the first volume of the trilogy, stands the name of Professor Gideon Greif, PhD, the Israeli historian and University Professor, expert for research of the Holocaust, particularly known worldwide for his research regarding Auschwitz. It is due to the comparison itself of two synonyms of evil, where the scale can adequately be seen of what is immeasurably less visible in the planetary framework, with what has become the focal point of the Holocaust remembrance, that the work of the author and his associates is of particular importance, with the emphasis on the specific features of Jasenovac camp and giving a broader context through other segments. This work encourages thinking and contributes to the remembrance culture, thus fulfilling the moral obligation towards the victims, which is also stressed by the author’s team.